Fecal microbiota transfer for refractory intestinal graft‐versus‐host disease — Experience from two German tertiary centers. (9th June 2021) - Goeser, Felix; Sifft, Barbara; Stein‐Thoeringer, Christoph; Farowski, Fedja; Strassburg, Christian P.; Brossart, Peter; Higgins, Paul G.; Scheid, Christoph; Wolf, Dominik; Holderried, Tobias A. W.; Vehreschild, Maria J. G. T.; Cruz Aguilar, Marta Rebeca
Abstract: Rationale: Steroid refractory graft‐vs‐host disease (sr‐GvHD) represents a challenging complication after allogeneic hematopoietic cell transplantation (allo‐HCT). Intestinal microbiota (IM) diversity and dysbiosis were identified as influencing factors for the development of acute GvHD. Fecal microbiota transfer (FMT) is hypothesized to restore IM dysbiosis, but there is limited knowledge about the significance of FMT in the treatment of sr‐GvHD. Objectives: We studied the effects of FMT on sr‐GvHD in allo‐HCT patients from two German tertiary clinical centers (n = 11 patients; period: March 2017 until July 2019). To assess safety and clinical efficacy, we analyzed clinical data pre‐ and post‐FMT (day ‐14 to +30 relative to FMT). Moreover, IM were analyzed in donor samples and in a subset of patients pre‐ and post‐FMT by 16S rRNA sequencing. Results: Post‐FMT, we observed no intervention‐associated, systemic inflammatory responses and only minor side effects (5/11 patients: abdominal pain and transformation of peristalsis—each 3/11 and vomiting—1/11). Stool frequencies and volumes were significantly reduced [pre‐ vs post‐FMT (d14): P < .05, respectively] as well as clear attenuation regarding both grading and staging of sr‐GvHD was present upon FMT. Moreover, IM analyses revealed an increase of alpha diversity as well as a compositional shifts toward the donor post‐FMT. Conclusions: In our study, we observed positive effects on sr‐GVHD after FMT without the occurrence of major adverse events. Although these findings are in line with published data on beneficial effects of FMT in sr‐GvHD, further randomized clinical studies are urgently needed to better define the clinical validity including mode of action.